Implementation of Active Learning Strategies - Hilmi Hilmi; Summiyani Summiyani (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2023)
The purpose of this research is to analyze the implementation of active learning strategies in the learning process in the classroom. This study uses the Library Research method, which is a literature study. The results of this study show that active learning strategies are a technique, strategy, or learning method that demands student activity, self-development, self-conceptualization, and meaning-building through various activities in the learning process so that learning objectives can be achieved effectively. In implementing this active learning strategy, the role of the teacher as an educator is very important. The position and role of the teacher are very strategic in active learning because the success or failure of students in learning is determined by the teacher's ability, creativity, and skills. If the educator is skilled and creative in teaching, it can be ensured that students will have a greater opportunity to be skilled, successful in learning, and thinking